Hyperactive Adverse Mechanical Stress Responses in Dystrophic Heart Are Coupled to Transient Receptor Potential Canonical 6 and Blocked by cGMP–Protein Kinase G Modulation - Kinya, Seo (2014)
Rationale: The heart is exquisitely sensitive to mechanical stimuli to adapt rapidly to physiological demands. In muscle lacking dystrophin, such as Duchenne muscular dystrophy, increased load during contraction triggers pathological responses thought to worsen the disease. The relevant mechanotransducers and therapies to target them remain unclear.Objectives: We tested the role of transient receptor potential canonical (TRPC) channels TRPC3 and TRPC6 and their modulation by protein kinase G (PKG) in controlling cardiac systolic mechanosensing and determined their pathophysiological relevance in an experimental model of Duchenne muscular dystrophy.Methods and Results: Contracting isolated papillary muscles and cardiomyocytes from controls and mice genetically lacking either TRPC3 or TRPC6 were subjected to auxotonic load to induce stress-stimulated contractility (SSC, gradual rise in force and intracellular Ca2+). Incubation with cGMP (PKG activator) markedly blunted SSC in controls and Trpc3−/−; whereas in Trpc6−/−, the resting SSC response was diminished and cGMP had no effect. In Duchenne muscular dystrophy myocytes (mdx/utrophin deficient), the SSC was excessive and arrhythmogenic. Gene deletion or selective drug blockade of TRPC6 or cGMP/PKG activation reversed this phenotype. Chronic phosphodiesterase 5A inhibition also normalized abnormal mechanosensing while blunting progressive chamber hypertrophy in Duchenne muscular dystrophy mice.Conclusions: PKG is a potent negative modulator of cardiac systolic mechanosignaling that requires TRPC6 as the target effector. In dystrophic hearts, excess SSC and arrhythmia are coupled to TRPC6 and are ameliorated by its targeted suppression or PKG activation. These results highlight novel therapeutic targets for this disease.